Liver Metastases in Pancreatic Acinar Cell Carcinoma Treated with Selective Internal Radiation Therapy with Y-90 Resin Microspheres - Felipe Nasser; Joaquim Maurício Motta Leal Filho; Breno Boueri Affonso; Francisco Leonardo Galastri; Rafael Noronha Cavalcante; Diego Lima Nava Martins; Vanderlei Segatelli; Lilian Yuri Itaya Yamaga; Rene Claudio Gansl; Bernardino Tranchesi Junior; Antônio Luiz de Vasconcellos Macedo (Case Reports in Hepatology)
Background. Pancreatic acinar cell carcinoma (PACC) is a rare tumor. Surgical resection is the treatment of choice when feasible, but there are no clear recommendations for patients with advanced disease. Liver-directed therapy with Y-90 selective internal radiation therapy (SIRT) has been used to treat hepatic metastases from pancreatic tumors. We describe a case of PACC liver metastases treated with SIRT. Case Report. 59-year-old man was admitted with an infiltrative, solid lesion in pancreatic tail diagnosed as PACC. Lymph nodes in the hepatic hilum were enlarged, and many metastatic liver nodules were observed. After partial pancreatectomy, the left and right lobes of the liver were separately treated with Y-90 resin microspheres. Follow-up imaging revealed that all hepatic nodules shrank by at least 50%, and 3 nodules disappeared completely. Lipase concentration was 8407 U/L at baseline, rose to 12,705 U/L after pancreatectomy, and declined to 344 U/L after SIRT. Multiple rounds of chemotherapy in the subsequent year shrank the hepatic tumors further; disease then progressed, but a third line of chemotherapy shrank the tumors again, 16 months after SIRT treatment. Conclusion. SIRT had a positive effect on liver metastases from PACC. In conjunction with systemic therapy, SIRT can achieve sustained disease control.